UTILIZING INNOVATIVE AND DIGITAL TECHNOLOGIES IN ORGANIZING SPORTS EVENTS - Berdiyev Dilmurod Nomonovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the role of innovative and digital technologies in organizing sports events. The integration of technology enhances planning, management, and execution processes, improving efficiency, accuracy, and participant engagement. Digital tools facilitate communication, scheduling, performance tracking, and interactive experiences, making sports events more accessible and engaging for students and participants. The study emphasizes the pedagogical and practical benefits of incorporating technology into sports event organization.